2006
DOI: 10.1111/j.1469-0691.2005.01289.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolving trends in infective endocarditis

Abstract: Infective endocarditis is a microbial infection of the endocardial surface and, despite improvements in diagnostic accuracy, medical therapy and surgical techniques, mortality remains high. This review focuses on changes in epidemiology, microbiology and diagnosis, as well as changes in medical and surgical management of infective endocarditis affecting native and prosthetic valves in adults, that have evolved during the past two decades. Significant changes have included an increasing involvement of prostheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
79
0
7

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(89 citation statements)
references
References 54 publications
(188 reference statements)
3
79
0
7
Order By: Relevance
“…In contrast to an earlier assumption that CoNS are more frequent in late-onset prosthetic vascular graft infections, there is no relationship between the microbiological pattern of infection, the time of infection onset, and the graft location (110). CoNS of the S. epidermidis group are still considered the most frequent cause of early prosthetic valve infective endocarditis (PVIE)-being responsible for 37 to 47% of early cases and about 25% of late cases, followed by S. aureus (20% and 11 to 21%, respectively) (111)(112)(113). A fatal early PVIE secondary to S. epidermidis, with a very aggressive progression, has been published (114).…”
Section: S Epidermidis Groupmentioning
confidence: 99%
“…In contrast to an earlier assumption that CoNS are more frequent in late-onset prosthetic vascular graft infections, there is no relationship between the microbiological pattern of infection, the time of infection onset, and the graft location (110). CoNS of the S. epidermidis group are still considered the most frequent cause of early prosthetic valve infective endocarditis (PVIE)-being responsible for 37 to 47% of early cases and about 25% of late cases, followed by S. aureus (20% and 11 to 21%, respectively) (111)(112)(113). A fatal early PVIE secondary to S. epidermidis, with a very aggressive progression, has been published (114).…”
Section: S Epidermidis Groupmentioning
confidence: 99%
“…In addition to colonizing the teeth in significant numbers, it is not unusual for S. mutans to gain access to the bloodstream during dental procedures (16,21,26). If a sufficient number of cells enter the circulation, transient bacteremia followed by adhesion to endothelial cells leads to infective endocarditis (IE) (26,37), particularly in persons with predisposing cardiac conditions.…”
mentioning
confidence: 99%
“…It is important for the surgeon to know whether a perivalvular abscess is present because if it is, the operative procedure is more complicated and is also associated with higher morbidity and mortality than in operations for simple valve replacement or repair for active IE (26). It has been shown that endocarditis caused by Staphylococcus aureus and other virulent microorganisms on valves in the left side of the heart are best treated with early surgery (26)(27)(28). In a large merged database on native valve endocarditis, the overall mortality was higher in patients with Staphylococcus aureus endocarditis than in those with other bacteria (20% vs. 12%, p= 0.001), but surprisingly, fewer patients infected with Staphylococcus aureus had surgery (26% vs. 39%, p= 0.001) (27).…”
Section: Discussionmentioning
confidence: 99%